States and the Making of Others - (:unkn) unknown (My University, 2024)
This volume offers a unique interdisciplinary and comparative perspective on contemporary processes of othering by state institutions in relation to dynamics of racism, xenophobia, sexism, homo-transphobia, as well as ethnic- and class-based discriminations. It focuses on eight original case studies empirically grounded in various domains of the ‘social state’, in Southern African and Western European contexts: the education and health care systems, the regulation of work and of procreation rights, and institutions in charge of granting asylum. The authors provide key insights on how states produce Others, and on how othering contributes in turn to the process of state formation and the politicization of public action.
Keywords: African Research